Strategi Pembelajaran Metacognitive-Scaffolding Untuk Meningkatkan Kemampuan Numerasi Siswa Kelas III SD Negeri Lembursawah 1 - Hopeman, Teofilus Ardian; Rahma, Aulia; Pradesa, Kohar (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
This study aims to determine the effectiveness of the application of metacognitive-scaffolding learning strategies to improve the numeracy skills of third-grade students of SD Negeri Lembursawah 1. Metacognitive-scaffolding learning is a learning strategy that helps students to involve their metacognitive abilities in the process and learning outcomes to improve students' numeracy skills, considering the lack of students' understanding of their numeracy skills. This is unfortunate because numeracy skills have as important a role as literacy skills. Through this numeracy ability, students are expected to be able to apply and solve various mathematical concepts in everyday life. The research method applied in this research is Classroom Action Research (CAR). The data collection instruments used were questionnaires, pre-tests, post-test, and document studies. The results showed that there was an increase in student learning outcomes after the implementation of the metacognitive-scaffolding learning strategy, which was indicated by an average value of 59.1 which was included in the Less category, while after the implementation of the action through the metacognitive-scaffolding learning strategy showed an increase that could be seen from the results of Post-Test cycle 2 with an average value of 70.2 in the Good category. Meanwhile in the Pre-Test cycle 1, the number of students who had not completed as many as 19 out of 42 students with 16 students in the Less category and 3 others in the Very Poor category. The increase in student learning outcomes also continued with the number of students who had not completed only 3 out of 42 students in the Less category after the Post-Test cycle 2 was implemented.